Pola Asuhan Kristen Christian Nurture Horace Bushnell dan Implementasinya Bagi Keluarga di Era Digital 4.0 - Dewi, Elisabeth Savitri Lukita (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
Abstract: Undeniably, we are living in the world of which high digital technology has developed so fast. This brings positive impacts to all the people. However, it also gives negative influence towards human-being, especially childrenâ€™s spiritual and mental growth. And as Christian parents living in the sophisticated world today, we have to be back to the Bible where parents have a very important role. Parents are commanded by God to be directly involved in nurturing and educating children. This study is intended to prove how important is Christian nurture and still relevant to be applied by the Christian parents. Based on the book â€˜Christian Nutureâ€™ written by Horace Bushnell, parents are the key to the growth of the children spiritually and mentally. To make the parents aware of their role and know how to do the role, Church must hold Christian education program â€œChristian Nurtureâ€ for the parents. By educating and empowering the parents, they will be able to nurture and educate the children. Parents and church have to work together to save the young generation.Keywords: nutur; role; parents; impact; growth; children.Abstrak:Tak bisa disangkali, kita hidup dalam dunia dimana teknologi digital berkembang begitu cepat. Hal ini membawa dampak positif bagi semua orang. Namun, hal ini juga berdampak negative terhadap manusia, khususnya bagi perkembangan rohani dan mental anak-anak. Dan sebagai orangtua Kristen yang hidup di dunia yang canggih hari-hari ini, kita harus kembali kepada Alkitab dimana orangtua memilili peranan penting. Orangtua diperintahkan Alla untuk langsung terlibat dalam mengasuh dan mendidik anak-anak. Studi ini bertujuan untuk membuktikan betapa penting asuhan Kristen dan masih trelevant diterapkan oleh para orangtua Kristen. Berdasarkan buku â€œAsuhan Kristenâ€ karangan Horace Bushnell, orangtua adalah kunci bagi pertumbuhan mental dan rohani anak-anak. Untuk menyadarkan para orangtua akan perannya dan bagaimana melaksanakan perannya, Gereja haruslah mengadakan program parenting â€œAsuhan Kristenâ€ bagi para orangtua. Dengan mendidik dan memberdayakan para orangtua, mereka akan mampu mengasuh dan mendidik anak-anak. Orangtua dan Gereja harus bekerja sama untuk menyelamatkan generasi muda.Kata kunci: asuhan, peran, orangtua, dampak, pertumbuhan, anak-anak.